HOME BIAS EFFECT IN PROSPECT OF FINANCIAL GLOBALIZATION - Kozyuk, Viktor (Journal of European Economy, 2017)
The author analyzes theoretical approaches to the problem of home bias effect. The tendency to a weakening home bias effect on the macro- and microlevels is shown empirically. The author asserts that this tendency roads to higher allocation efficiency of global capital markets and the capacity of the macropolicy to level out consumption. However, it also bears certain risks from the global financial stability perspective.